Minimal configuration of body surface potential mapping for discrimination of left versus right dominant frequencies during atrial fibrillation. Issue 8 (12th July 2017) - Rodrigo, M.; Climent, A.M.; Liberos, A.; Fernández‐Aviles, F.; Atienza, F.; Guillem, M.S.; Berenfeld, O.
Abstract: Background: Ablation of drivers maintaining atrial fibrillation (AF) has been demonstrated as an effective therapy. Drivers in the form of rapidly activated atrial regions can be noninvasively localized to either left or right atria (LA, RA) with body surface potential mapping (BSPM) systems. This study quantifies the accuracy of dominant frequency (DF) measurements from reduced‐leads BSPM systems and assesses the minimal configuration required for ablation guidance. Methods: Nine uniformly distributed lead sets of eight to 66 electrodes were evaluated. BSPM signals were registered simultaneously with intracardiac electrocardiograms (EGMs) in 16 AF patients. DF activity was analyzed on the surface potentials for the nine leads configurations, and the noninvasive measures were compared with the EGM recordings. Results: Surface DF measurements presented similar values than panoramic invasive EGM recordings, showing the highest DF regions in corresponding locations. The noninvasive DFs measures had a high correlation with the invasive discrete recordings; they presented a deviation of <0.5 Hz for the highest DF and a correlation coefficient of >0.8 for leads configurations with 12 or more electrodes. Conclusions: Reduced‐leads BSPM systems enable noninvasive discrimination between LA versus RA DFs with similar results as higher‐resolution 66‐leads system. Our findings demonstrate the possible incorporation of simplified BSPM systems into clinical planning procedures for AF ablation.